The challenge of abandonment for the sustainable management of Palaearctc natural and semi-natural grasslands - Valko, Orsolya; Venn, Stephen; Zmihorski, Michal; Biurrun, Idoia; Labadessa, Rocco; Loos, Jaqueline (Hacquetia, 2018)
Disturbance by biomass removal is a crucial mechanism maintaining the diversity of Palaearctic grasslands, which are unique biodiversity hotspots. Te century-long traditional land use of mowing, grazing and burning, has been fundamentally changed in many parts of the Palaearctic. Due to socio-economic changes, large areas of former pastures and meadows have been abandoned, leading to a succession towards secondary scrublands or forest and the encroachment of competitor grass species, all leading to a decrease in biodiversity. Here we report the causes and consequences of the cessation of traditional grassland management regimes, provide strategies for reducing the impact of abandonment and consider these from the perspective of sustainability. We consider the possibilities for initiating sustainable management regimes in the contemporary socio-economic environment, and discuss the prospects and limitation of alternative management regimes in the conservation of grassland biodiversity. Tese themes are also the core topics of this Special Feature, edited by the EDGG. We hope that this Special Feature will encourage steps towards more sustainable strategies for the conservation of Palaearctic grasslands and the integration of the sustainability perspective into their conservation.